1985
DOI: 10.1111/j.1476-5381.1985.tb16151.x
|View full text |Cite
|
Sign up to set email alerts
|

Central effects of nicotinamide and inosine which are not mediated through benzodiazepine receptors

Abstract: 1The actions of nicotinamide and inosine were investigated on rat cerebellar Purkinje cells using ionophoretic and extracellular recording techniques. 2 lonophoretic application of nicotinamide or inosine showed that they were potent inhibitors of Purkinje cell firing. This inhibition differed from that induced by benzodiazepines in that it was not reversed by the GABA antagonists bicuculline methiodide and picrotoxin. RO 15-1788

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Inosine potentiates adenosine-induced vasodilation of pial arterioles, presumably via inhibition of adenosine uptake (Ngai et al, 1989). Inosine has been shown to produce inhibitory responses in rat cerebellar Purkinje cells (Bold et al, 1985), mouse spinal cord neuronal cultures (MacDonald et al, 1979), rat cortical neurons (Phillis et al, 1975), and guinea~pighippocampal slices (Alzheimer et al, 1991). Inosine"aiso appears to elicit a rapidly desensitizing excitatory response in mouse spinal cord neuronal cultures (MacDonald et al, 1979).…”
Section: Figmentioning
confidence: 99%
“…Inosine potentiates adenosine-induced vasodilation of pial arterioles, presumably via inhibition of adenosine uptake (Ngai et al, 1989). Inosine has been shown to produce inhibitory responses in rat cerebellar Purkinje cells (Bold et al, 1985), mouse spinal cord neuronal cultures (MacDonald et al, 1979), rat cortical neurons (Phillis et al, 1975), and guinea~pighippocampal slices (Alzheimer et al, 1991). Inosine"aiso appears to elicit a rapidly desensitizing excitatory response in mouse spinal cord neuronal cultures (MacDonald et al, 1979).…”
Section: Figmentioning
confidence: 99%
“…These effects depend on the expression of the GABA A R β3 subunit (Laposky, Homanics, Basile, & Mendelson, 2001), but direct evidence for these compounds binding to the BZ-binding site and activating the GABA A R is lacking. Other small molecule candidate ligands including inosine, hypoxanthine, and nicotinamide have low affinity for the GABA A R BZ-binding site and are present in low concentrations in the brain and thus are unlikely to represent the natural physiological relevant endozepines (Asano & Spector, 1979; Bold, Gardner, & Walker, 1985; Lapin, 1980; Tallman, Paul, Skolnick, & Gallager, 1980). …”
Section: Candidate Endozepinesmentioning
confidence: 99%
“…For example, nicotinamide can function as an anxiolytic [128], increase brain choline levels [72], and act as an endogenous ligand for benzodiazepine receptors [129]. Additional work has indicated that nicotinamide can increase cell tolerance against vascular thermal injury and increase capillary density [130].…”
Section: Nicotinamide Progenitor Cells and Cellular Proliferationmentioning
confidence: 99%